THE CONCEPT OF HUMAN RIGHTS IN THE DIGITAL ERA/ CHANGES AND CONSEQUENCES FOR JUDICIAL PRACTICE - Razmetaeva, Yulia; Barabash, Yurii; Lukianov, Dmytro (Access to justice in Eastern Europe, 2022)
The digital age has led to conceptual changes in human rights and their content, understanding, implementation, and protection. Discussions about expanding the range of both addressees and subjects of human rights are a consequence and, at the same time, a breeding ground for change. New challenges for rights related to technological development, the increasing influence of companies and organisations, the growing use of solutions based on artificial intelligence, and the habit of relying on such solutions have led to the need for a substantial revision of such aspects as the content of individual rights and their catalogue, the definition of the fourth generation of rights as bio-information, and the clarification of the concept of digital rights. Digitalisation, which in a broad sense represents the legal, political, economic, cultural, social, and political changes caused by the use of digital tools and technologies, covers the private and public spheres, revives our understanding of and research into human rights in a horizontal dimension, and influences the revision of their anthropological foundations. The general philosophical framework of this research consisted of axiological and hermeneutic approaches, which allowed us to conduct a value analysis of fundamental human rights and changes in their perception, as well as to apply in-depth study and interpretation of legal texts. The study also relied on the comparative law method in terms of comparing legal regulation and law enforcement practice in different legal systems. The method of legal modelling was used to highlight the bio-information generation of human rights as the fourth generation of rights, as well as some scientific predictions in the field of human rights. The article argues that it is necessary to change our approach to human rights in the digital era, to widen the circle of addressees of human rights obligations to include companies and organisations, and to be ready potentially recognise artificial intelligence as a subject in public relations and fundamental rights. The term ‘spectrum of algorithm-based digital technologies’ is proposed, which can more accurately describe those phenomena that are covered by the synonymous terms ‘artificial intelligence’ and ‘algorithm’. The article proposes to consider digital rights in three dimensions, as well as to take into account the subtle structural consequences of changing the concept of human rights in the digital era for judicial practice.